An (un)answered cry for help: a qualitative study exploring the subjective meaning of eating disorders in the context of transgenerational trauma - Jennifer Barry; John O’Connor; Harriet Parsons (Journal of Eating Disorders)
Abstract Background Current research on the transmission of trauma and eating disorders across generations is limited. However, quantitative studies suggest that the influence of parents’ and grandparents’ eating disorders and their prior exposure to trauma are associated with the development of eating disorders in future generations. Qualitative research exploring personal accounts of the impact of transgenerational trauma on the development of eating disorders has been largely unexplored. The aim of the current qualitative study was to explore the meaning that participants ascribed to their eating disorders in the context of transgenerational trauma across three generations. Methods Six adult female participants who had received a diagnosis of anorexia nervosa and/or bulimia nervosa completed multiple unstructured interviews, informed by a psychoanalytical methodology. Results Four themes were developed from the material that emerged from the interviews: (1) The toll of undigested emotions (2), A need for safety (3), “It’s not just me” – making connections with the past, and (4) “Last link” in the chain? Conclusions The themes were discussed in respect of previous literature, with a particular emphasis on Gerson’s concept of the dead third, which emphasises an unconscious compulsion to repeat unprocessed transgenerational traumas. Clinical implications of the research underscores the importance of a holistic approach to the treatment of eating disorders, recognising both individual and familial traumas within the family system. Moreover, the research demonstrates the significant impact that mental health clinicians can have in eating disorder treatment by fostering a supportive, safe and trusting therapeutic relationship.